Intellectual property valuation, infringement, and infringement damages - Parr, Russell L. (John Wiley & Sons, 2018)
"Intellectual Property simplifies the process of attaching a dollar amount to intellectual property and intangible assets, be it for licensing, mergers and acquisitions, loan collateral, investment purposes, and determining infringement damages.